2021
DOI: 10.3389/fmicb.2021.722052
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer Substances and Safety of Lactic Acid Bacteria in Clinical Treatment

Abstract: Lactic acid bacteria (LAB) are a kind of Gram-positive bacteria which can colonize in the biological gastrointestinal tract and play a variety of probiotic roles. LAB have a wide range of applications in industry, animal husbandry, planting, food safety, and medical science fields. Previous studies on LAB have typically concentrated on their effects on improving the digestion and absorption of the gastrointestinal tract, regulating the balance of the microflora, and inhibiting the production and accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…Large numbers of studies involving in vitro (employing immune and cancer cell lines) and in vivo (cancer induced in mice and rats) evaluation of these potential anticancer and antitumor activities of LAB have been reported (Azam et al, 2014 ; Chondrou et al, 2018 ; El Ghany et al, 2015 ; Hwang et al, 2022 ; Nami et al, 2014 ; Saxami et al, 2016 ; Tukenmez et al, 2019 ; Tuo et al, 2015 ; Zhou et al, 2017 ). Very recently, Liu et al ( 2021a ) provided a mini-review of the anticancer substances from LAB, including the EPS, peptidoglycan, nucleic acid, bacteriocin, and S-layer proteins; while Wu et al ( 2021 ) focused on the anticancer effects and mechanism of EPS from LAB. As anticancer and antitumor activities and potentials of LAB are commonly evaluated by wet lab experiments, genome analysis is usually complementary to these studies by assessing the quality and safety of the strains (Tegopoulos et al, 2021 ).…”
Section: Screening For Genes That May Provide Direct Health Benefits ...mentioning
confidence: 99%
“…Large numbers of studies involving in vitro (employing immune and cancer cell lines) and in vivo (cancer induced in mice and rats) evaluation of these potential anticancer and antitumor activities of LAB have been reported (Azam et al, 2014 ; Chondrou et al, 2018 ; El Ghany et al, 2015 ; Hwang et al, 2022 ; Nami et al, 2014 ; Saxami et al, 2016 ; Tukenmez et al, 2019 ; Tuo et al, 2015 ; Zhou et al, 2017 ). Very recently, Liu et al ( 2021a ) provided a mini-review of the anticancer substances from LAB, including the EPS, peptidoglycan, nucleic acid, bacteriocin, and S-layer proteins; while Wu et al ( 2021 ) focused on the anticancer effects and mechanism of EPS from LAB. As anticancer and antitumor activities and potentials of LAB are commonly evaluated by wet lab experiments, genome analysis is usually complementary to these studies by assessing the quality and safety of the strains (Tegopoulos et al, 2021 ).…”
Section: Screening For Genes That May Provide Direct Health Benefits ...mentioning
confidence: 99%
“…[ 42 ] To increase the competitiveness of bacteria in nutrient plundering at the tumor site, a series of nanocatalysts have been designed to participate in the metabolism and growth of bacteria to increase the consumption of nutrients by bacteria. [ 43 ] As a result, various efforts to synergistically integrate nanomedicine with attenuated bacteria to develop enhanced tumor treatments have mushroomed in the past five years. [ 44 ] However, a comprehensive review to summarize the role of bacteria in nanobiohybrid cancer therapy, the synergic effect of bacteria and nanomedicine in tumors, and the development of multimodal synergistic cancer therapy facilitated by bacteria are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…With nearly 10 million deaths by 2020, cancer remains one of the major challenges of the 21st century ( 9 ). Recent studies have shown that LAB can inhibit the onset or progression of cancer in various ways, which has potential clinical value in cancer prevention and treatment ( 10 ).…”
Section: Introductionmentioning
confidence: 99%